DETERMINANTS OF JAPAN MANUFACTURING EXPORT PERFORMANCE - Rynalto Mukiwihando (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
Export has been believed as an ultimate engine for economic growth. There are many tools to boost export performance. Among of them are foreign networks, RD activities and firms’ size. A bigger opportunity of overseas market, innovative products and competitive prices are the expected outcome of applying those aforementioned settings within the segmented businesses. This paper aims to obtain empirical insight of the factors that may influence export performance. Employing Japanese manufacturing sector export performance, as one of the leading industries in the world, the study explore the linkage between those three preceding factors to export performance improvement in Japan. Study results shows that research and development activities as well as firm’s size play critical roles within the improvement of Japanese manufacturing export performance. Whereas foreign networks, which denoted by foreign subsidiaries, has an insignificant positive contribution to export performance. Future studies may give in-depth focus on the foreign networks issues within a longer period of study. The implication of this study is addressing these two essential issues, RD activities and firms’ size, to the policy making processes in achieving optimal results of manufacturing export performance